Moral emotions and physiological markers in prosocial decision-making - Santana, Ana Paula Souza (2019)
The present study aimed to investigate the effects of prototypical moral emotions on prosocial behavior in an economic task, in interaction with physiological markers of arousal, measured through Electrodermal Response and Heart Rate, and of parasympathetic response, measured through Heart Rate Variability. 40 undergraduate and postgraduate students performed an experimental version of the Ultimatum Game with moral vignettes describing the responders. We found that participants’ mean offer in the elevation block was higher than in the outrage block. The physiological measures did not differ significantly between both emotional blocks. The results suggested that information people receive about third-parties influence their behavior towards them, through moral judgment. Therefore, the results are in line with the assumption that emotions elicited by a disinterested elicitor can influence one’s decision to help or not a third-party